1994
DOI: 10.1108/09513549410069202
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Planning in Higher Education

Abstract: The Education Reform Act 1988 brought about a number of radical changes in the structure and funding of UK higher education institutions particularly within the “new university” and college sector. As a result, they now operate within a much greater competitive context and need therefore to incorporate a greater market orientation into their strategic planning process in order to acquire a competitive advantage over their rivals. Reports on exploratory research undertaken to assess the degree to which these hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
18

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 18 publications
0
88
0
18
Order By: Relevance
“…Therefore, the role of the brand in communicating the institution's values and identity to consumers becomes more prevalent as a strong brand reduces risk in decision making. Although there is some resistance to the notion of students as customers (Barrett, 1996;Conway, Mackay, & Yorke, 1994), some authors argue that HE is people-based, reflecting the key nature of services marketing (Binsardi & Ekwulugo, 2003;Mazzarol, 1998;Nguyen & LeBlanc, 2001;Parasuraman, Zeithaml, & Berry, 2003). However, the concept of brand image and reputation may be interpreted differently in HE compared with other services organizations, necessitating studies with a specific focus for the HE context.…”
Section: Brand Identitymentioning
confidence: 99%
“…Therefore, the role of the brand in communicating the institution's values and identity to consumers becomes more prevalent as a strong brand reduces risk in decision making. Although there is some resistance to the notion of students as customers (Barrett, 1996;Conway, Mackay, & Yorke, 1994), some authors argue that HE is people-based, reflecting the key nature of services marketing (Binsardi & Ekwulugo, 2003;Mazzarol, 1998;Nguyen & LeBlanc, 2001;Parasuraman, Zeithaml, & Berry, 2003). However, the concept of brand image and reputation may be interpreted differently in HE compared with other services organizations, necessitating studies with a specific focus for the HE context.…”
Section: Brand Identitymentioning
confidence: 99%
“…To begin, the lack of clearly-demarcated student veteran services mission statements is troublesome: only 12 institutions, representing 24% of the sample, featured student veteran services mission statements on their institutional websites. Given the importance of how an institutional mission statement articulates the goals, priorities, and resources of a given institution (Conway, Mackay, & Yorke, 1994;Fugazzotto, 2009;Morphew & Hartley, 2006), student veteran services offices need to better communicate their purposes and functions to their prospective and current student veteran population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, institutional mission statements are often written by a collective leadership aware of the complexity of a student's role within an institution, equating a student to a customer receiving a variety of educational services. As a result, institutions of higher education constantly assess and reassess the student's role within their institution to refine and redefine institutional strategies for maximizing resources to serve students based on the articulation of a mission statement (Conway, Mackay, & Yorke, 1994). Given this flux, recent research on postsecondary mission statements found that such statements provide two chief institutional benefits: to help organizational members delineate between institutional and non-institutional activities and promote a shared, stable sense of purpose in order to inspire and motivate all organizational members to uphold and share that purpose with others.…”
Section: Significance Of a Higher Education Mission Statementmentioning
confidence: 99%
“…Más aún, Conway et al (1994) afirman que las instituciones educativas superiores han incrementado la aplicación de estrategias y políticas de marketing a fin de poder ajustarse a las demandas del entorno. Así, y de acuerdo con Küster-Boluda y Vila-López (2012), existen ciertas evidencias que constatan que las teorías y conceptos de marketing pueden ser aplicados en el contexto educativo y, en especial, en el ámbito de la educación superior.…”
Section: Introductionunclassified